The Cinematic Art (History) and Mieke Bal’s Thinking in Film - Lipiński, Filip (Artium Quaestiones, 2020)
The article focuses on Mieke Bal’s theoretical considerations of art in terms of film and movement in general. This cinematic frame offers her a conceptual framework for “thinking in film”, a way to rethink not only diverse forms of art, moving and still images, but also, as I argue, methodological models for art history. The text begins with a general outline of the tensions and relations between art history and film/film studies, with a discussion of several cases of the theoretical application of film in the field of art history. Bal’s case, the main subject of the article, is perhaps the most consistent and theoretically advanced attempt at reconceptualizing diverse aspects of art in interdisciplinary, cinematic terms within a larger phenomenon which might called a theoretical dimension of the “cinematic turn”. While I acknowledge the importance and complementary nature of Bal’s artistic practice as a video artist with her theoretical work, due to the limited space of this article, the focus of my text is on her writing. I closely trace and discuss a variety of Bal’s texts, predominantly written over the last 20 years, in which she theorizes and analyzes works in which movement is either explicit, such as video or video installation or implicit, such as painting. In her crucial, relevant books, Thinking in Film. The Politics of Video Installation According to Eija-Liisa Athila (2013) or Emma&Edvard Looking Sideways: Loneliness and the Cinematic, Bal, referring to a number of scholars and thinkers, but most prominently and consistently to Henri Bergson, points to four kinds of movement: literal or represented movement of/in the image, movement related to perception, affective movement and, finally, its political dimension, all of which are discussed in this article. Video installation is an art form which for Bal becomes the best concretization (a contact space) of all of the above aspects of movement, activating “thinking in film”. This involves new reformulations of spatial and temporal dimensions of art, with such concepts as heterochrony and timespace. Moreover, with reference to video art, Bal coined the notion of “migratory aesthetics”, where migration not only literally concerns migrants and immigration but offers a platform to reflect on and renegotiate the issues of movement, stagnation, the everyday and their political dimensions. Last but not least, film, according to Bal, also offers a useful framework for analyzing the experience of art exhibitions. In discussing Bal’s work, I argue that her “cinematic”, conceptual travels in art offer a radical opening of a number of art historical categories and procedures, and I propose to regard her project of “thinking in film” as indicative of a larger changes across disciplines already visible in her earlier work in the 1990s, which involve the productive redefinition of historical and temporal experience, mobilization of perception and the body, relational mode of thinking and vision, affective dimension of experiencing art and the acknowledgment of agency both on the part of the viewer and the artwork.